641 A CONTROVERSIAL CASE OF FABRY DISEASE: ADDING ANOTHER PIECE TO THE INTERPRETATION PUZZLE OF C.376A>G MISSENSE MUTATION, A PATHOGENIC VARIANT. (15th December 2022) - Indennidate, Carla; Faganello, Giorgio; Sinagra, Gianfranco; Di Lenarda, Andrea
Abstract: Background: The association between chronic neuropathic pain in childhood, left ventricular hypertrophy(LVH), early ischemic stroke and unexplained renal failure is suggestive of FD. However, because of the heterogeneity of the genetic substrate, different and more subtle phenotypic manifestations are possible as well as single organ involvement. Diagnostic criteria require an initial measurement of both alpha-galactosidase A (α-Gal-A) activity levels in leukocytes and globotriaosylsphingosine (LysoGb3, a glycosphingolipid derivative) concentration. Genetic testing is needed to confirm the diagnosis if α-Gal-A is decreased or absent and Lyso-Gb3 is increased. Case report: A 35-year-old man was referred to our outpatient cardiology clinic at the beginning of summer 2022. He had a family history of sudden death, he had no cardiovascular risk factors and a history of severe acral pain during childhood. On medical background, he had undergone renal transplantation after two years of hemodialysis therapy due to nephroangiosclerosis and tubulointerstitial nephritis, identified in renal biopsy. On physical examination were visible neither angiokeratomas nor ocular manifestations. ECG showed LV hypertrophy and a transthoracic ECO confirmed LV concentric hypertrophy, a preserved LV ejection fraction and the presence of unexplained subtle LV systolic dysfunction due to an abnormal LV global longitudinal strain. Laboratory tests revealed normal serum creatinine and elevated NT-ProBNP levels. Unfortunately, a CMR examination was not performed because of the patient's claustrophobia. Genetic and enzymatic analyses were performed on the high suspicion of a cardiac storage disorder. The enzymatic activity of α-Gal-A and lyso-Gb3 concentration was within normal values, whereas genetic analysis detected a missense mutation (c.376A>G) in exon 3 causing an amino acid substitution (p.S126G). The suspicion of FD was confirmed. Discussion: This is an interesting case with a diagnosis of FD that is controversial for several reasons. The c.376A>G is a rare mutation, found mainly in female patients with normal α-Gal-A and LysoGb3 levels ​​and associated with isolated renal failure. In addition, this variant is typically responsible for the late onset of the disease, occurring after 40 years of age 2, 8–11 . Our patient is young and presents early cardiac and severe nephrological involvement, both typical clinical features of FD. A normal activity of α-Gal-A is consistent with the missense gene mutation: enzyme activity appears to be normal up to at least 90-95% reduction of function. To date, there is little evidence in the scientific literature of similar cases and the clinical presentations associated with this mutation are contradictory. Since 2002, c.376A>G has been known to be a pathogenetic variant of FD 12, in 2010 it was associated to late-onset disease 13 . However, in the International Fabry Disease Genotype-Phenotype Database, it is considered a likely benign variant of FD 2 . Conclusion: In this case report, we emphasize that high clinical suspicion should lead to more diagnostic evaluations, including genetic testing in the daily routine. Additional studies are needed to better understand the role of the c.376 A>G mutation in the FD.